Green Technological Attributes of Clean Water and Green Energy : Fostering the Public Health, Economic and Environmental Sustainability - Shahidul, Islam; Malcolm Mussen, Lamoh; Shahnur, Begum (TFE Global (M) Sdn. Bhd, 2025)
This book explores the technological attributes of green energy for clean water. Titled “Green Technological Attributes of Clean Water and Green Energy,” it aims to present a roadmap for optimizing green energy for sustainable clean water production and supply, achieving zero carbon emissions to safeguard public health and the environment. The energy demand in the water sector is increasing due to the growing need for surface water and wastewater treatment to meet rising water demands. Simultaneously, water demand itself is increasing due to global warming and population growth. This highlights the complex relationship between energy and water, a relationship that must be addressed to tackle clean water scarcity and mitigate the effects of climate change. In this context. This book is published to provide information related to green energy and clean water. This book aims to disseminate research outcomes related to green technologies for clean water and green energy, contributing to the replacement of traditional water treatment systems powered by fossil fuels and chemical dosing This book showcases experimental results on the energy requirements for clean water production and delivery to end-users in rural villages in Sarawak, Malaysia. It is part of a broader study exploring the energy-water nexus within the context of zero-carbon emission and chemical-free water services. Focusing on the water industry, this book explains the need for green energy in clean water production. A multi-dimensional scientific approach has been employed to minimize carbon emissions. Marginalized communities living in off-grid areas can benefit from this book by learning how to harvest green energy from nature to produce clean water. This book also benefits society by providing information on green technologies for harvesting natural resources. A key global challenge is overcoming the lack of green energy for clean water production, and this book will contribute to addressing this challenge. Communities working on clean water production using green energy will find the information they need in this book. The information published in this book can serve as a reference for further research on green technology for clean water production. Researchers, water professionals, and environmental scientists can find guidelines for the green technological attributes of designing and developing water filtration plants. This book can also inform policymakers developing strategies for clean water production with optimal energy consumption, zero carbon emissions, and no chemical dosing in water filtration.